Interactive Digital Media Integration in Problem-Based Learning to Improve Critical Thinking Skills of Middle School Students - Erwanto; Gilang Kartika Hanum; Sumihatul Ummah MS; Muhammad Arsyad; Meriyati (Jurusan Teknik Informatika dan Komputer, 2025)
This study aims to examine the effectiveness of integrating interactive digital media into problem-based learning (Problem-Based Learning/PBL) to enhance the critical thinking skills of middle school students. The research method used is a quantitative approach with a quasi-experimental pretest-posttest control group design. The subjects of the study are 60 eighth-grade students at SMP Negeri 4 Bandar Lampung, divided into experimental and control groups. The instruments used include critical thinking skills tests based on Ennis’ indicators, as well as observation sheets for learning activity engagement. The data were analyzed using normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, as well as N-Gain and Cohen’s d calculations. The results indicate a significant increase in critical thinking skills in the experimental group compared to the control group, with a p-value of 0.000 in the independent t-test. The average N-Gain for the experimental group was 50.88% (moderate category), while the control group only achieved 3.48% (low category). The effect size calculated using Cohen’s d reached 3.08, indicating a very large treatment effect. These findings reinforce that integrating interactive digital media into problem-based learning can effectively improve students’ critical thinking skills. The results also support the implementation of the Merdeka Curriculum, which emphasizes strengthening the Pancasila student profile, especially in the dimensions of critical and reflective thinking.